2009
DOI: 10.2135/cropsci2008.05.0242
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Bioassay Method Influences Detection of Annual Bluegrass Resistance to Mitotic‐Inhibiting Herbicides

Abstract: Dinitroaniline‐resistant annual bluegrass (Poa annua L.) has been reported in several states; however, there are no standardized screening methods for detecting resistance. Research was conducted to evaluate screening techniques (Murashige and Skoog [MS] media, filter paper, hydroponics, and soil based) to detect herbicide resistance to dithiopyr, prodiamine, and pendimethalin in a suspected resistant ecotype of annual bluegrass from Chattanooga, TN (Chattanooga). A senstitive ecotype from Fresno, CA (Control)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 17 publications
2
44
0
Order By: Relevance
“…Prodiamine rates needed to reduce dry biomass of the resistant and susceptible phenotypes by 50% were 1,006 and 45 g ha −1 , respectively, equating to a resistance factor of 22 based on dry biomass reductions. These results are similar to research conducted by Cutulle et al (2009), who identified a phenotype of annual bluegrass 26 times less sensitive to prodiamine than a known susceptible phenotype.…”
Section: Confirming Resistance In Progenysupporting
confidence: 89%
“…Prodiamine rates needed to reduce dry biomass of the resistant and susceptible phenotypes by 50% were 1,006 and 45 g ha −1 , respectively, equating to a resistance factor of 22 based on dry biomass reductions. These results are similar to research conducted by Cutulle et al (2009), who identified a phenotype of annual bluegrass 26 times less sensitive to prodiamine than a known susceptible phenotype.…”
Section: Confirming Resistance In Progenysupporting
confidence: 89%
“…While both dinitroaniline herbicides and dithiopyr both inhibit mitosis, dithiopyr does so in a slightly different fashion (Cutulle et al, 2009). Unlike dinitroanilines, dithiopyr has preemergence activity and postemergence activity on certain weeds-primarily Digitaria spp.…”
Section: Preemergence Herbicidesmentioning
confidence: 99%
“…These herbicides disrupt mitosis by preventing the protein tubulin from polymerizing to form microtubules required for cell division (Vaughn & Lehnen 1991). Multiple biotypes of annual bluegrass resistant to the DNA herbicide prodiamine have been reported in the southeastern United States as the result of repeated use of prodiamine for residual control of annual weeds (Cutulle et al 2009;Isgrigg et al 2002;Lowe et al 2001). Certain prodiamine-resistant annual bluegrass populations have also shown reduced sensitivity to another DNA herbicide, pendimethalin (Cutulle et al 2009).…”
Section: Resistance To Mitotic Inhibitorsmentioning
confidence: 99%
“…Multiple biotypes of annual bluegrass resistant to the DNA herbicide prodiamine have been reported in the southeastern United States as the result of repeated use of prodiamine for residual control of annual weeds (Cutulle et al 2009;Isgrigg et al 2002;Lowe et al 2001). Certain prodiamine-resistant annual bluegrass populations have also shown reduced sensitivity to another DNA herbicide, pendimethalin (Cutulle et al 2009). Seed of DNAresistant and -susceptible biotypes have similar germination rates; however, above ground growth of DNA-resistant annual bluegrass and foxtail (Setaria spp.)…”
Section: Resistance To Mitotic Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation